The Correlation between the Dimention of Trust among the Member of the Group and the Effectiveness of PBL Tutorial Group - Istadi, Yani (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2011)
Background: The tutorial plays a central role in problem-based learning (PBL). The effective implementation of small group tutorials is one of the key contributors to the students success in examinations. This study aimed to identify factors perceived as the predictors for effectiveness of PBL group tutorial.Design and method: The subjects of the study were all of the students (year of 2008) of the Medical College of Sultan Agung Islamic University taking the Tropical Disease Module. The adapted version of the scales adopted in this study included the scale developed by Van den Bossche et al for assessing team (group) effectiveness, trust dimension and learning behavior, a scale developed by Dolmans & Ginns (2005) for assessing tutor’s performance, a 5 points likert scale was used to asses the student opinions. Quantitative approach with correlation and multiple regression analysis was applied.Result: Of 238 students included in the study 84 (37.3%) were male and 139 (62.3%) were female. There was a significantly positive correlation between the trust dimension related to the interpersonal relationship among the members of tutorial group with the effectiveness of tutorial group ( r = 0.631, p< 0.01). There was a medium correlation among cohesion, group potency and psychological (r= 0,700, p < 0.05 there was correlation among the variables of (r = 0,557, p < 0,001), group potency (r = 0,517, p < 0,001), and psychological assurance (r = 0,437, p < 0.001). These three variables contributed to the group effectiveness as much as 48.4% with a F value of 87.857. The component of independence was not found to be the predictive factors for group effectiveness. The correlations among the variables of cohesion, group potency and psychological assurance resulted in contingency coeficien of 0.700 with p<0.05.Conclusion: The higher trust related to the interpersonal relationship among the member of groups, the more effective the group will be. Cohesion, group potency and psychological assurance were found to be the predictive factors for group effectiveness (Sains Medika, 3(1):16-23).